Amyand's Hernia: A Serendipitous Diagnosis. (4th April 2013) - Mewa Kinoo, S.; Aboobakar, M. R.; Singh, B.
Abstract : An Amyand's hernia refers to the presence of an appendix within an inguinal hernia sac. This uncommon finding occurs in less than 1% of all right side inguinal hernias; to date, this finding has been reported in only 14 patients with left side inguinal hernias. The preoperative diagnosis of this condition is uncommon. We report the 15th case of a left side Amyand's hernia that was diagnosed preoperatively on a contrast enema study as well as the relatively more common right-sided Amyand's hernia diagnosed serendipitously at surgery.